Eksplorasi Air Tanah di Desa Langori, Kecamatan Baula, Kabupaten Kolaka, Menggunakan Metode Resistivitas Schlumberger - Usmardin Usmardin; Jahidin Jahidin (Jurnal Rekayasa Geofisika Indonesia, 2024)
Efforts have been made to search for subsurface water sources using geophysical methods, namely the Schlumberger resistivity method by mapping groundwater resources. This research aims to determine the existence of groundwater resources in the Kolaka Regency area, especially Langori Village, Baula District. Data collection was carried out at two measuring locations and processed using Progress. The results show a profile of groundwater resistivity values of 3.32 Ωm – 48.96 Ωm at a depth of 4.92 m to 370 m. It is suspected that the groundwater layer for measuring location point 1 or line 1 is at several depths, 8.57 m - 9.42 m, 13.30 m - 27.22 m, 166.28 m - 188.36 m, and 249.78 m - 370 m, each of which has a resistivity value of 26.95 Ωm, 6.52 Ωm, 31.54 Ωm, and 31.82 Ωm. Measuring location point 2 or line 2, the suspected groundwater layer is found at a depth of 4.92 m - 8.55 m, 20.53 m - 31.60 m, and 70.73m - 117.42 m, respectively each has a resistivity value of 41.91 Ωm, 3.32 Ωm, and 32.11 Ωm.